Individual differences in the effectiveness of self‐distancing for young children's emotion regulation. (15th July 2018) - Grenell, Amanda; Prager, Emily O.; Schaefer, Catherine; Kross, Ethan; Duckworth, Angela L.; Carlson, Stephanie M.
Abstract : Self‐distancing has been shown to improve children's self‐regulation in a variety of tasks. However, it is unknown whether this strategy is more effective for some children than others. This study investigated self‐distancing in relation to individual differences in executive function (EF) and effortful control (EC). Typically developing 4‐ ( n  =   72) and 6‐year‐olds ( n  =   67) were randomly assigned to think about the self from one of four perspectives: self‐immersed, control, third‐person, or competent media character. Children participated in a frustrating task for up to 10 min and overt expressions of frustration were coded. Conceptually replicating prior research with adults, younger children, and children with lower EF and lower EC (independent of age) benefitted the most from self‐distancing. This suggests self‐distancing is especially effective during a frustrating task for children with less developed self‐control, adding to a growing body of research showing self‐distancing is especially effective for vulnerable individuals. Statement of contribution What is already known on this subject? Using third‐person speech and pretending to be a media character improve children's self‐regulation. Age and theory of mind skills are related to the effectiveness of self‐distancing. What does this study add? Self‐distancing can help children regulate their emotions during an emotionally charged task. Individual differences in executive function and effortful control are related to the efficacy of self‐distancing.